Agama, Budaya, dan Negara: Formulasi Nasionalisme dalam Pemikiran Nahdlatul Ulama dan Muhammadiyah - Nasih Al Hashas, Mohammad; Luqman Hakim, Ahmad; Alfaridzih, Achmad (Zawiyah: Jurnal Pemikiran Islam, 2025)
Nahdlatul Ulama (NU) and Muhammadiyah are the two largest Islamic organizations in Indonesia and the primary global representations of Ahlussunnah wal Jamaah Islam. Although both belong to the Sunni branch of Islam, they differ in ideology and organizational orientation. NU represents traditional Islam that accommodates the acculturation of religion and culture, while Muhammadiyah depicts a modern-urban Islam that tends to draw a line between religious and cultural dimensions. Regarding nationalism, both organizations share a strong commitment to nationalism, but NU's expression of patriotism is considered more prominent than Muhammadiyah's. These differences are influenced by the social background of its members, their scientific genealogy, and their respective conceptions of the relationship between religion and state. This research uses a literature study approach with a descriptive-qualitative method, namely collecting, reviewing, and interpreting primary and secondary sources related to the history, ideology, and religious discourse of both organizations. The analysis is conducted through thematic reading and comparison of key concepts regarding nationalism in each organization. The research results show that NU and Muhammadiyah are both committed to strengthening Indonesian national identity, but have different styles of expression and patriotic orientations. NU is more prominent in the symbolic-cultural articulation of nationalism, while Muhammadiyah emphasizes a rational-modern approach to national contribution. This difference indicates that the two complement each other in building an inclusive Indonesian nationalism rooted in religious tradition.